KEBIJAKAN PEMERINTAH PERIHAL PENGANGKATAN TENAGA HONORER TERHADAP BERLAKUNYA PERATURAN PEMERINTAH NOMOR : 56 TAHUN 2012 TENTANG PENGANGKATAN TENAGA HONORER MENJADI CALON PEGAWAI NEGERI SIPIL DI LINGKUNGAN PEMERINTAH KABUPATEN MAPPI PROVINSI PAPUA - WIDOYO, WAHYU (Dinamika Hukum, 2018)
The Objectives of research is to analyze the Government Regulation No 56 of 2012. abaout the Honorary officer Hiring into the Potential Civil Servants implemented in the Government of Regency Mappi viewed from the law implementation aspect and to evaluate the implementation of Governmant Regulation No 56. of 2012 implementation in coping with the problems of officer hiring in Regency Mappi.In fact, in order to support the smoothness of government and development assignment implementation, in both central and local government, the honorary officers are hired. Among those honorary officers some of them had been working for along time for the governmernt and their existences are really necessary to the government. In order to cope with the problems of honorary officer, the government issues policy goverming the honorary officers hiring into Potential Civil Servants (CPNS). With the philosophy of desiring to recruit the Potential Civil Servant (CPNS) from honorary officer as appreciation for their dedication to the government, the Government Policy is issued in the form of Government Regulation No, 56 of. 2012. about the Honorary Officer Hiring into the Potential Civil Servants. The research method used in this study was sociological law research, because it started from the primary data , the one deriving directly from the society as the first source using field study that was conducted using observation and interview. The law research as sociological ( empirical ) research can be realized in the law implementation prevailing or the research on law identification. This research was taken place in Badan Kepegawaian Pendidikan dan Latihan Aparatur of Regency Mappi to facilitate the access to the source and information on the data needed in this research and because the writer resides in the research location area so that observation, study and analysis level on the research object is expected to be more precisely.The result of discussion using analysis shows that the implementation of honorary officer hiring into the potencial civil servants in Regency of Mappi has not effective because some obstacles and problems are found during implementation of honorary officer hiring into the Potential Civil Servants in Regency of Mappi Key words : Obstacles, Impementation, appointmen of honorery staff